Kajian Kondisi Lingkungan Kerja Sebagai Penunjang Kinerja Karyawan PT. Hasjrat Multifinance - Kaparang, Yolanda . (JURNAL ILMIAH SOCIETY, 2015)
This research discussed the work environment condition in supporting the performance of employees in PT. Hasjrat Multifinance.This research is based on both physical and nonphysical issues experienced by the employees while they are working. Noisy environment is one of the physical issues and relationship between the management and employees is one of the non physical issues. The aforementioned issues signified that PT. Hasjrat Multifinance has not yet created an ideal working condition for the employees.It is a qualitative research. The informants of this research are the employees of PT. Hasjrat Multifinance Manado. The data have been collected by interviews, observation and documentation. The researcher also discovered that in terms of nonphysical work condition, particularly one that deals with social relationship, the horizontal relationship is better than the vertical one because the effort to create conducive environment has been done more by employees who have so far established and maintained good relationship among them.Even though competition and personal issues are unavoidable but they did not affect the existing horizontal relationship in general. Therefore, the harmonious horizontal relationship has been providing comfort and secure feeling for the employees when working together. Key Words: Work Environment Support, Performance of Employees